A pobreza e a dinâmica espacial do trabalho nos frigoríficos de aves no oeste paranaense - Silva, Gabriel Rodrigues da (2010)
This research looked for to understand the implications of the industrial employment in the West of Paraná, specifically in the refrigerating industries of birds, contemplating about the possible transformations for the workers' life, that is to say, if it is possible to affirm that through this employment in the butcher shops there is improvement for the life conditions. This way, the objective of this work went research to expansion of the industrial capitalism in this area, the economic activity that stands out in the area it is the agricultural production gone back to the soy cultivation and corn with strong performance of the cooperatives, however, these companies pass to act not just in the commercialization of grains, but also in the productive chain of the chicken meat with strong expansion of the employment. Another prominence of the research is regarding the study in the ways and concepts that the poverty assumes, starting from the varied researched references, assuming direct relationship with the inadequacy of income, therefore having intrinsic relationship with the insert of the poor population in the labor market and in the case, in the butcher shops of birds. Starting from the reflections and mainly starting from the workers' of the butcher shops of birds depositions it is possible to affirm that the characteristics of the generated employments are related to the extreme degradation of the worker's health, with several problems of health, long work day and deterioration of the family contact, if on one side the employment facilitated access to the signed work wallet, for other, it presents degradation of the workers' life, inside and out of the work. It is like this perceptible that the poverty doesn't just show in the workers that are out of the formal labor market, but in the ambit of the formal employment.